2017
DOI: 10.1055/s-0043-116223
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Feasibility of Electronic Patient-Reported Outcome (ePRO) Data Entry in the PRAEGNANT Real-Time Advanced and Metastatic Breast Cancer Registry

Abstract: Purpose Patient-reported outcomes (PROs) have been incorporated into clinical trials for many symptoms and medical conditions. A transition from paper-based capture of PROs to electronic PROs (ePROs) has recently started. This study reports on the feasibility of ePRO assessment in a prospective registry including molecular data for patients with advanced breast cancer. Methods As part of the PRAEGNANT network, patients were invited by clinical trial staff, physicians, and nurses to complete three sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
2
16
0
6
Order By: Relevance
“…Furthermore, some hospitals were not able to assist participants in downloading the BRE-4-MED APP or online questionnaire due to problems with highly secured firewalls in some hospitals. Wallwiener et al reported similar challenges on usage of electronically PROs in the "Prospective Academic translational research network for the optimization of oncological health care quality in the advanced setting" (PRAEGNANT) registry [9]. The process chosen for record linkage with both established Cancer Registries (Bavaria and Baden-Wuerttemberg) worked out without any problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some hospitals were not able to assist participants in downloading the BRE-4-MED APP or online questionnaire due to problems with highly secured firewalls in some hospitals. Wallwiener et al reported similar challenges on usage of electronically PROs in the "Prospective Academic translational research network for the optimization of oncological health care quality in the advanced setting" (PRAEGNANT) registry [9]. The process chosen for record linkage with both established Cancer Registries (Bavaria and Baden-Wuerttemberg) worked out without any problems.…”
Section: Discussionmentioning
confidence: 99%
“…8 Centre of Early Cancer Detection and Cancer Registration, Bavarian Health and Food Safety Authority, Nürnberg, Germany. 9 Bavarian Health and Food Safety Authority, Munich, Germany. 10 Department of Medical Psychology and Psychotherapy, Medical Sociology and Rehabilitation Sciences, University of Würzburg, Würzburg, Germany.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ein weiteres Feld, auf dem sich digitale Ansätze für die Onkologie abzeichnen, ist die digitale Verlaufskontrolle unter einer Tumortherapie. Die Sinnhaftigkeit einer Implementierung von elektronisch erhobenen Daten zum "patient-reported outcome" (ePRO) wurde durch zahlreiche Arbeitsgruppen publiziert [7]. Darüber hinaus konnte gezeigt werden, dass digitale Tools einen hohen Stellenwert beim sogenannten Follow-up entfalten können [8,9].…”
Section: Digitales Follow-upunclassified
“…The application is implemented in the PRAEGNANT multicenter trial for patient-reported outcome data collection in metastatic breast cancer [7]. Furthermore, patient adoption, even within the age range of over 60 years, has been high [8].…”
Section: Digital Follow-upmentioning
confidence: 99%